2021
DOI: 10.1088/1755-1315/948/1/012058
|View full text |Cite
|
Sign up to set email alerts
|

Field evaluation of the combination of larvicide and rice stem immersion to improve lethal ovitrap effectiveness in dengue vector control

Abstract: The combination of temephos and attractants from O.sativa was effective for lethal ovitrap in laboratory testing. However, the effectiveness of the field application needs further investigation. The study’s objective was to determine the influence of ovitrap installation sites, season variation, and attractant on lethal ovitrap efficacy. The study used a quasi-experimental design. Lethal ovitraps were installed indoors and outdoors in 102 houses and observed for 14 weeks. Statistical analysis was conducted wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Although not statistically supported, field tests conducted in Semarang and Salatiga (Indonesia) using lethal ovitraps revealed a decrease in Ae. aegypti population density [ 26 , 27 ]. According to a field study, lethal ovitrap control programs significantly impacted Ae.…”
Section: Mechanical Methodsmentioning
confidence: 99%
“…Although not statistically supported, field tests conducted in Semarang and Salatiga (Indonesia) using lethal ovitraps revealed a decrease in Ae. aegypti population density [ 26 , 27 ]. According to a field study, lethal ovitrap control programs significantly impacted Ae.…”
Section: Mechanical Methodsmentioning
confidence: 99%
“…In Brazil and Australia, dengue fever outbreaks were controlled by installing lethal ovitraps to reduce the density of Aedes aegypti, an environmentally friendly method (Perich et al, 2003;Long et al, 2015). In the city of Semarang, city of Salatiga and city of Makassar, it has been shown that the use of ovitrap attractants can reduce the density of dengue vectors (Ermayana et al, 2015;Pujiyanti et al, 2021).…”
Section: Introductionmentioning
confidence: 99%